Organizational Commitment Mediates the Effect of Transac-tional Leadership on Turnover Intention on Frontliners - Wafiq Nuril Azizi; Ika Korika Swasti (Digital Innovation : International Journal of Management, 2025)
The high level of turnover intention in frontliner employees is a serious challenge for retail companies, including CV. Premium Indonesia. This study aims to analyze the effect of transactional leadership on turnover intention mediated by organizational commitment. This research uses a quantitative approach with survey techniques on 56 frontliner respondents. The results showed that transactional leadership has a negative influence on turnover intention. This means that the more effective the application of transactional leadership style, the lower the employee's intention to leave the company. In addition, organizational commitment also negatively affects turnover intention and is proven to be able to mediate the relationship between transactional leadership and turnover intention. These findings confirm the important role of leadership and commitment in retaining the workforce, especially in the dynamic and competitive retail sector.